TEACHING WRITING FOR ADULT LEARNERS (Academicia Globe: Inderscience Research, 2022)
This article clearly explains how important role writing plays in teaching all learners, including adults. In this article the reason why writing is considered to be the core aspect in the progress of learners in other necessary English competences, speaking, reading, listening, is thoroughly discussed.